Optimization of Specific Productivity for Xylonic Acid Production by Gluconobacter oxydans Using Response Surface Methodology - He, Tao; Xu, Chaozhong; Ding, Chenrong; Liu, Xu; Gu, Xiaoli (Frontiers in Bioengineering and Biotechnology, 2021)
Large amounts of xylose cannot be efficiently metabolized and fermented due to strain limitations in lignocellulosic biorefinery. The conversion of xylose into high value chemicals can help to reduce the cost of commercialization. Therefore, xylonic acid with potential value in the construction industry offers a valuable alternative for xylose biorefinery. However, low productivity is the main challenge for xylonic acid fermentation. This study investigated the effect of three reaction parameters (agitation, aeration, and biomass concentration) on xylose acid production and optimized the key process parameters using response surface methodology (RSM). The second order polynomial model was able to fit the experimental data by using multiple regression analysis. The maximum specific productivity was achieved with a value of 6.64±0.20 g gx-1 h-1 at the optimal process parameters (agitation speed 728 rpm, aeration rate 7 L min-1, and biomass concentration 1.11 g L-1). These results may help to improve the production efficiency during xylose acid biotransformation from xylose.